Long-term storage of yacon (Smallanthus sonchifolius) juice: Phytochemical profile, in vitro prebiotic potential and discriminant bioactive properties. (June 2021) - Marques, Caroline; Bortolan Toazza, Carlos Eduardo; Sari, Rafael; Mitterer-Daltoé, Marina Leite; Amaral, Wanderlei do; Masson, Maria Lucia
Abstract: Yacon ( Smallanthus sonchifolius ) is a plant, with South American origin, whose roots received the designation of functional food due to fructan-type sugars and phenolics in its composition. Aiming to keep yacon beneficial compounds in long-term storage, a new food formulation was proposed, being prebiotic yacon juice preserved by lactobionic (LBA) and malic acids. Thus, yacon juice was evaluated regarding its prebiotic potential in vitro, bioavailability of phenolic compounds and bioconversion of sugars. Discriminant analysis with canonical correlation pointed out Fe2+ chelation, color, pH, total extractable polyphenols and prebiotic potential as the discriminating parameters among samples, during refrigerated storage of 120 days (6 °C ± 2 °C). The essential role of LBA and malic acid addition was confirmed as they kept: pH at desirable levels, a stable color profile, Fe2+ chelating activity at values between 30-40% until day 30, bioavailability of polyphenols up to 13% maximum loss, and almost doubled the shelf-life. Chromatographic profile by HPLC corroborated these findings, which verified a more solid hydrolysis of fructan-type sugars in the yacon juice without acids. Resultant molds and yeasts limited the shelf-life to 60 days for the control sample, and 105 days for the acid-added ones. In addition, unprecedented prebiotic potential of yacon juice was confirmed: to Lactobacillus casei and Lactobacillus acidophilus for at least 120 days and for 105 days for Bifidobacterium animalis . Lastly, the LBA, an alleged prebiotic compound, had no prebiotic-enhancing activity, possibly due to the amount (1%) applied. Graphical abstract: Image 1 Highlights: Yacon prebiotic juice, preserved with malic and lactobionic acids, was proposed. Phytochemical profile showed phenolic and sugar bioconversion during storage. Molds and yeasts limited shelf life of yacon juice in 105 and 60 days (control). Prebiotic potential was confirmed to L. casei, L. acidophilus and B. animalis . Fe 2+ chelation, color, pH, polyphenols and prebiotics discriminated the juices.